A REVIEW ON NICOTINE FOR HEALTH: INSIGHT FOR “PRO-HEALTH” NICOTINE USAGE - PRIBADI, FLORENCE; SANTOSA, RAHAJOE IMAM; DARMANTO, ARIEF GUNAWAN (International Journal of Current Pharmaceutical Research, 2020)
Nicotine is a major chemical of tobacco that makes smokers having difficulties to stop consuming cigarette. That chemical is an alkaloid-based plant and known for one of the major compound of cigarette. Many researches showed the negative side of nicotine. In contrast, a recent study showed the benefits of nicotine. Some researches proved that nicotine has high possibility to improve the depressive behavior both in animal models and human subject. In addition, more research also proved that nicotine has cognitive-enhancing effects, which means it has the ability to improve the function of working memory, episodic memory, attention, and fine motor function. The current review deliberates about the good side and the diversity usage of nicotine, particularly in medicine, as novel therapeutics for neurodegenerative diseases.